Volatile Constituents and Antimicrobial Activities from Flower and Fruit of Arbutus unedo L. - Kahriman, Nuran; Gulec Albay, Canan; Dogan, Nese; Usta, Asu; Alpay Karaoglu, Sengul; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
Essential oils isolated by hydrodistillation from flower and fruit of Arbutus unedo growing in Turkey were analyzed by GC and GC/MS. Forty-nine compounds, representing around 95 % of the total oils were identified. Non-terpenoids hydrocarbons were shown to be the main group of constituents of the flower and fruit part of the plant in the ratio of 62.2 and 92.8 %, respectively. The major component in the essential oil of the flower was a-terpineol (16.3 %) and the main compound in the essential oil of the fruit was hexadecanoic acid (21.7 %). The antimicrobial activity of the isolated essential oils of the flower and fruit were also investigated and it showed moderate antibacterial activity against Listeria monocitogenes and Enterococcus faecalis.